This is Not a Nest - Jean-Pierre Chupin (Footprint)
Although the architecture competition has been analysed through a number of rhetorical lenses, the recurring production of transcultural metaphors, particularly in international competitions, remains to be addressed as a genuine disciplinary phenomenon. The hypothesis of competitions as contact zones is particularly appropriate for the study of international events, in which competitors forge broad analogical figures to bridge cultural differences. Recent studies in the cognitive understanding of analogical matrices have considerably reinforced the theories on metaphors. Our analytical grid characterizes analogical matrices to identify levels of symbolic operations through the differentiation of formal, structural and conceptual analogies. We first dig into a sample of competition projects nicknames (Crystal, Birds’Nest, DNA, Cloud, Lace, Stealth, etc.) to confirm that these tropes have a paradoxical status at the intersection of architects’ intents and the public expectations. We then summarize an in-depth hermeneutical discourse analysis of 40 North American international competitions. This indicates a fourfold series of expectations to which competitors hope to provide answers in an international ‘conflict of interpretations’. Adhering to the theory of speech acts, we suggest that performative metaphors in competitions appear less as indicators of designers’ intentions than as products of the broader context surrounding competitions themselves. We conclude with a proposed grid indexing four types of contact zones in which metaphorical relationships are actively created and not just repeated.